TEM STUDIES AND THE SHOCK HISTORY OF A "MYSTERITE" INCLUSION FROM THE KRYMKA LL CHONDRITE - Weber I.; Stephan T.; Jessberger E.K.; Semenenko V.P. (My University, 2006)
The microstructure and composition of the matrix of one carbonaceous inclusion (K1) in the Krymka LL3.1 chondrite were studied using transmission electron microscopy (TEM). K1 has previously shown an enigmatic nature and similarities with volatile-rich, fine-grained, dark inclusions of Krymka called "mysterite." In the present study, four m inerals were identified by TEM. Olivine, pyroxene, and pyrrhotite typically have grain sizes of one micrometer; graphite occurs as flakes of a similar size. Olivine shows a moderately high dislocation density most probably caused by shock. Pyroxene shows coexisting ortho- and clinoenstatite lamellae that probably originated from shear stress after a shock event or from the rapid cooling of the protoenstatite stability field. However, we demonstrate that in this case, a shock trigger is more likely. Pyrrhotite in the studied sample occurs as a 4C monoclinic superstructure. The graphite flakes in the fragment are well crystallized, as can be seen by discrete spots in the diffraction pattern. In graphite, the degree of crystallization increases with the metamorphic grade. Based on the microstructure of this mineral we conclude that after a first moderate shock event, the residual temperature between 300 °C and 500 °C led to thermal metamorphism. A second shock event, possibly at excavation from the parent body, is responsible for the shock features observed in olivine, pyroxene, and graphite. © The Meteoritical Society, 2006.